ASN002 demonstrates efficacy and improves inflammation in AD. (1st October 2019) - Bissonnette, R.; Maari, C.; Forman, S.; Bhatia, N.; Lee, M.; Fowler, J.; Tyring, S.; Pariser, D.; Sofen, H.; Dhawan, S.; Zook, M.; Zammit, D.J.; et al.
Summary: Few medicines are available for the treatment of moderate‐to‐severe atopic eczema. ASN002 is a new oral (taken by mouth) drug being tested that has been shown to reduce the activity of various proteins playing a role in skin inflammation. In the present study, the safety and efficacy of different doses of ASN002, administered once daily for 4 weeks, were evaluated and compared to a placebo in patients with moderate‑to‑severe eczema. The placebo was a tablet made from the same base product used to make ASN002, but that did not contain any active medication. A total of 27 patients received ASN002 and nine patients received the placebo. In general, ASN002 was well tolerated and caused limited side effects, with higher doses of ASN002 not causing more frequent or severe side effects. After four weeks of treatment, patients who received ASN002 had a better improvement in the severity of their eczema compared to patients who received the placebo, and these positive effects were noted as early as two weeks following the start of treatment. Treatment with ASN002 also rapidly improved the degree of itch and was associated with a significant reduction in the level of proteins circulating in the blood that are involved in inflammation. Taken together, the encouraging efficacy and safety profile of ASN002 warrants further investigation of ASN002 in patients with moderate‑to‑severe eczema.